RELEVANSI KITAB TA’LIIMUL MUTA’ALLIM TERHADAP PENDIDIKAN KARAKTER SANTRI - Ulin Ni'mah Rodliya Ulfah; Bisri Mustofa (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Strengthening moral education or character education in the current context is very relevant to overcome the moral crisis that is currently occurring. This is a qualitative study that aims to find out how the process of teaching character education is in Islamic boarding schools, especially in the Al Amin Ngasinan Rejomulyo Kediri Islamic boarding school and the relevance of the Ta'liimul Muta'allim book to the formation of character education for its students. From the data analyzed, it was found that: 1. The process of teaching character education in the Al-Amin Ngasinan Rejomulyo Kediri Islamic boarding school is carried out using four methods, namely: lecture method, question and answer method, exemplary method (uswah hasnah) and advice method. 2. The character values ​​contained in the Ta'liimul Muta'allim book are relevant to the vision and mission of the Al-Amin Ngasinan Rejomulyo Kediri Islamic boarding school, so this book is appropriate if used as material for teaching character education in the Islamic boarding school. This suitability lies in its sources, namely the Qur'an and Al-Hadith.